(untitled) (Bangladesh Journal of Nuclear Medicine, 2019)
In a Single Photon Emission Computed Tomography (SPECT) study, the data acquisition is performed over a relatively long time, typically in the range of 5-30 minutes. For longer period, patient movement frequently occurs in clinical procedure. This movement causes misalignment of the projection frames,which degrades the image quality. In this work, different SPECT studies by using Hoffman 3D brain phantom without motion were acquired and by using algorithm, the motion induced data were simulated from these real data. Different data without motion were acquired by using a Trionix Triad triple-head SPECT camera withthe phantom. Simulated data were evaluated and Mean Square Differences (MSD) was calculated using two differently developed algorithms. These simulated data were produced by adding projection framespartiallywith the aim to produce a new data set so that it simulates motion induced data. We calculated the MSD from the simulated data by analyzing each projection frame. The result showsthe significant MSD values between two different projection frames which were obtained from two different SPECT acquisitions. Motion induced simulated data is useful in quantifying motion estimation and to develop correction methods that will allow derivation of motion free data. Bangladesh J. Nuclear Med. 21(1): 31-34, January 2018